2003
DOI: 10.1046/j.1462-5822.2003.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusalpha-toxin induces apoptosis in peripheral blood mononuclear cells: role of endogenous tumour necrosis factor-alpha and the mitochondrial death pathway

Abstract: SummaryStaphylococcus aureus infections can result in septic and toxic shock with depletion of immune cells and massive cytokine production. Recently, we showed that, in S. aureus -infected Jurkat T cells, a a a a -toxin is the major mediator of caspase activation and apoptosis. Here, we investigated the mechanisms of cell death induced by a a a a -toxin in peripheral blood mononuclear cells (MNC). We show that a a a a -toxin is required and sufficient for S. aureus -induced cell death not only in transformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 55 publications
8
91
1
1
Order By: Relevance
“…These results are consistent with the eliminated transcription of hla expression in vitro in this study and previous reports (11,22). Our unpublished data and studies by other investigators have demonstrated that alpha-toxin is necessary for S. aureus to cause different types of cell apoptosis and death via different signaling transduction pathways (2,14,25,33). Furthermore, in this study we demonstrated that the SaeRS system plays an important role in S. aureus pathogenesis in a murine model of infection.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with the eliminated transcription of hla expression in vitro in this study and previous reports (11,22). Our unpublished data and studies by other investigators have demonstrated that alpha-toxin is necessary for S. aureus to cause different types of cell apoptosis and death via different signaling transduction pathways (2,14,25,33). Furthermore, in this study we demonstrated that the SaeRS system plays an important role in S. aureus pathogenesis in a murine model of infection.…”
Section: Discussionsupporting
confidence: 93%
“…Besides its capability to induce necrosis, ␣-toxin has been reported to generate, at subcytotoxic concentrations, small, monovalent cation-selective pores leading to cell activation and death through the activation of the intrinsic apoptotic pathway (1,12). We looked for features of apoptosis in cells exposed to S. aureus for periods shorter than 24 h. Excitingly, by two different approaches, we showed that at 8 h postinfection a high percentage of cells exhibited characteristics of apoptotic cells and that during S. aureus infection, cells entered in an apoptotic process that was rapidly followed by necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…From our results, Alpha hemolysin protein had high inhibitory activity against HepG-2 and HCT-116, and had weak inhibitory activity against MCF-7 and A-549. In this connection, Haslinger et al (2003); Essmann et al (2003) had reported that S. aureus α-toxin is a pore-forming toxin that can caused apopotosis of tumor cells at higher concentrations. In this study, it was found that the cell viability of MCF-7 was represented 78.95% per 48 hours.…”
Section: Application Of Recombinant α-Hemolysin Protein In Different mentioning
confidence: 99%